Interpreting the Consequences of Midwestern Agricultural Industrialization - King, Martin Burce (Journal of Economic Issues (Association for Evolutionary Economics), 2000)
The article focuses on the interpretation of consequences of Midwestern agricultural industrialization. The nature and consequences of the industrialization of agriculture are well documented in academic research and in the popular press. Interpretations of the process vary in reflection of the diverse perceptions of the nature and overall significance of industrialization. Suggested policies range from a "hands-off" to a "prohibit and prevent wherever possible" approach. Both approaches are unrealistic because they fail to recognize the historical context in which agricultural industrialization is taking place. In this paper, the author presents a historical context for the process, using nineteenth-century Illinois and the industrialization of swine production as examples of commercialization and industrialization of Midwestern agriculture, respectively. The author integrates the work of Karl Polanyi and K. William Kapp into the discussion to provide a foundation for realistic policy and to demonstrate the relevance of an institutionalist perspective to the formation of contemporary agricultural policy.
Keywords: KAPP, Karl William; agriculture; commercialization; crop insurance; economic theory; evolutionary economics; industrialization; production (economic theory); rural industries

The Reproving of Karl Polanyi - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2000)
Karl Polanyi's The Great Transformation has had enormous influence since its publication in 1944. In form, this influence has been salutary: Polanyi targets one of the main weaknesses of modern economics. But in substance, Polanyi's influence has been baneful. Mirroring the methodological blindness he criticizes, Polanyi insists on the all-or-nothing existence/nonexistence of laissez faire--and on its all-or-nothing goodness/badness.
Keywords: critique; history of economic thought: individuals

Freedom and the Market (An Analysis of the Anti-globalization Movement from the Perspective of the Theoretical Foundation of the Evaluation of the Dynamics of Capitalism by Polanyi, Hayek and Keynes.) - Nikitin, Pavel V.; Elliott, John E. (Forum for Social Economics, 2000)
Those who believe that the free market is positively related to both economic efficiency and individual freedom are prone to regard resistance to the establishment of the global market essentially free from any serious sociopolitical constraint as a politically insignificant expression of impatience, ignorance, and hypocrisy. This article attempts to endow the manifestation of discontent with the status quo evident in public protests in Seattle and Washington DC with political significance through explicating it as an expression of a fundamental conflict between economic efficiency and individual freedom inherent in the global implementation of the principle of self-regulating markets. This analysis of the anti-globalization movement is conducted from the perspective of the theoretical foundation of the evaluation of the dynamics of capitalism by Polanyi, Hayek, and Keynes, and its conclusions are brought to bear upon the validity of their contesting views of the relationship between economic efficiency and individual freedom.
Keywords: anti-globalization movement; capitalist systems; international economic order; political economy

Karl Polanyi's Forms of Integration as Ways of Mapping - Schaniel, William C.; Neale, Walter C. (Journal of Economic Issues, 2000)
Researcher Karl Polanyi's "forms of integration"--redistribution, reciprocity, and exchange--have been much used to describe and explain various economies. Such mapping presents information about the sources and destinations of the flows of material means in each society in ways that are easily correlated with the variables that most thoroughly and simply account for the flows of material means in different societies. Mapping may be looked upon as the selection of a "projection" for portraying the flows of material means. The diagrams below illustrate the discussions of each form of integration and are examples of mapping. As is the case for projections selected for geographical mapping, for each way of mapping a form of integration the criterion of the appropriateness of the choice of projection is analogous to a mathematical function. The independent variables would be information about the social system; the dependent variable would be the directions in which the material means flow. The merits of the choice of projection are simplicity and the accuracy with which the directions of flow are portrayed.
Keywords: commercial policy; economics; forms of integration; functions; mappings (mathematics); mathematics; social sciences